Celebrating Participatory Governance in Nueva Vizcaya - Jimenez, Pilar R.; Masulit, Saniata P.;Mendoza, Ysadora F. (Manila, Philippines : Social Development Research Center, De La Salle University, 2004)
The Philippines is currently undergoing economic, social, political, and cultural transformation, which can be attributed to globalization, decentralization, and rapid urbanization. Decentralization, in particular has brought about changes as well as challenges that local government units (LGUs) must address.
Chapter One: Process and elements of participatory governance -- Chapter Two Cases of participatory governance in selected development areas -- Chapter Three: Issues and implications -- Chapter Four: Sustainability: participatory governance!.
Keywords: POLITICAL PARTICIPATION -- PHILIPPINES -- NUEVA VIZCAYA